Coffee consumption and risk of pancreatic cancer: a systematic review and dose–response meta-analysis. (4th July 2019) - Li, Tian-Dong; Yang, Hong-Wei; Wang, Peng; Song, Chun-Hua; Wang, Kai-Juan; Dai, Li-Ping; Shi, Jian-Xiang; Zhang, Jian-Ying; Ye, Hua
Abstract: The association between coffee consumption and pancreatic cancer risk has been extensively studied; however, there is no consistent conclusion. Therefore, this meta-analysis study sought to evaluate dose–response relationship between them. A search was conducted using the PubMed and Web of Science databases. Thirteen high-quality cohort studies were identified, involving in 959, 992 study participants and 3831 pancreatic cancer cases. Comparing the highest with lowest categories of coffee intake, the pooled relative risk (RR) was 1.08 (95% CI 0.94–1.25). For dose–response analysis, no evidence of a nonlinear dose–response association between coffee consumption and pancreatic cancer ( p for nonlinearity =0.171) was found. The risk of pancreatic cancer was increased by 5.87% (RR =1.06, 95% CI 1.05–1.07) with the increment of one cup/day. Coffee consumption was identified to be related with the increasing risk of pancreatic cancer in a dose–response manner. Nevertheless, further mechanistic studies are needed to clarify the concerned issues.